Correlation Between Financial Performance Indicators and Capital Structure of Coal Mining Industry Listed on the Indonesia Stock Exchange - Yansil, Eko Thio Ady; Sumirat, Erman Arif; Nainggolan, Yunieta Anny (Integrasi Sains Media, 2023)
This research examines the correlation between capital structure (as proxied by Debt-to-Equity Ratio) and several financial performance indicators, including profitability, asset structure, liquidity, and firm size. This research focuses on 18 coal mining companies listed on the Indonesia Stock Exchange (IDX) by at least 2020. The data is derived from the financial reports published on the IDX between 2020 and 2022. Multiple Linear Regression technique is being employed to determine the correlations. Before employing the Multiple Linear Regression technique, several tests were conducted to examine the data's validity and reliability, including normality, multicollinearity, autocorrelation, and heteroscedasticity tests. Multiple Linear Regression is employed after the data passes the tests, consisting of partial regression, ANOVA, and goodness-of-fit tests. This research found that profitability and liquidity negatively correlate with capital structure. At the same time, asset structure and firm size positively correlate with capital structure. Overall, the result of this research supports Pecking Order Theory, in which firms are preferred to use internal financing first. When firms generate higher profits and cash flow, they may consider re-balancing external financing. This research also concludes that profitability, asset structure, liquidity, and firm size represent 47.7% of the variables correlated with capital structure. Future research may be conducted to seek other variables that have not been included in this research yet but are correlated with capital structure.